2015
DOI: 10.1002/hbm.22851
|View full text |Cite
|
Sign up to set email alerts
|

Decreased activity with increased background network efficiency in amnestic MCI during a visuospatial working memory task

Abstract: Recent studies have demonstrated the working memory impairment in patients with amnestic mild cognitive impairment (aMCI). However, the neurophysiological basis of the working memory deficit in aMCI is poorly understood. The aim of this study was to explore the abnormal activity during encoding and recognition procedures, as well as the reorganization of the background network maintaining the working memory state in aMCI. Using event-related fMRI during a visuospatial working memory task with three recognition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 89 publications
0
27
0
Order By: Relevance
“…As a key structure in working memory processing, the PFC exerts control over behavior by biasing the salience of mnemonic representations and adjudicating among competing context-dependent rules (D’Esposito and Postle, 2015 ). Previous studies found that MCI patients show significantly decreased activity in the PFC and significantly increased activity in the parietal-occipital regions during working memory tasks (Bokde et al, 2010 ; Lou et al, 2015 ). Consistent with these findings, the PFC and parietal occipital-regions showed group × state interactions in our study.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…As a key structure in working memory processing, the PFC exerts control over behavior by biasing the salience of mnemonic representations and adjudicating among competing context-dependent rules (D’Esposito and Postle, 2015 ). Previous studies found that MCI patients show significantly decreased activity in the PFC and significantly increased activity in the parietal-occipital regions during working memory tasks (Bokde et al, 2010 ; Lou et al, 2015 ). Consistent with these findings, the PFC and parietal occipital-regions showed group × state interactions in our study.…”
Section: Discussionmentioning
confidence: 94%
“…In addition, the working memory component of our task was not very pure because processing consisted of encoding, retrieval, and sub-resting sessions (for details, see “Materials and Methods” Section). Given the observation of decreased activity in different regions during the encoding and retrieval processes of a spatial working memory task in MCI patients (Lou et al, 2015 ), future studies should separate these two subprocesses to explore whether brain oscillations vary according to these subtypes in working memory states.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These ndings raise the opportunity that the cerebellum is not a "silent bystander" in AD, and the cerebellum may not be an optimal choice for the reference region. With the development of neuroimaging, growing studies reported the cerebellar atrophy and functional alteration in AD [8][9][10][11][12][13]. However, till now, the studies about the changes of cerebellum in AD patients are still limited, and results are not consistent.…”
Section: Introductionmentioning
confidence: 99%